PIMREG is a prognostic biomarker involved in immune microenvironment of clear cell renal cell carcinoma and associated with the transition from G1 phase to S phase - Yao, Huibao; Lyu, Feifei; Ma, Jian; Sun, Fengze; Tang, Gonglin; Wu, Jitao; Zhou, Zhongbao (Frontiers in Oncology, 2023)
Background: Clear cell renal cell carcinoma (ccRCC) is one of the most common tumors in the world and affects human health seriously. PIMREG is a mitotic regulator which is essential to the metaphase-to-anaphase transition in cell cycle. Although PIMREG plays a crucial role in the malignant progression of tumors, there are few reports on its role in ccRCC. Methods: The transcriptional expression profile and clinical data of PIMREG were downloaded from TCGA database and verified by qRT-PCR. Kaplan-Meier plotter was used to analyze the effect of PIMREG on overall survival (OS), disease specific survival (DSS) and progression-free interval (PFI) of patients with ccRCC. Univariable and multivariable Cox regression analysis were used to determine the independent prognostic factors of ccRCC. The effects of PIMREG on cell migration and invasion were detected by wound healing assay and transwell invasion assay, and CCK-8 assay, colony formation assay and cell cycle assay were used to detect the effect of PIMREG on cell proliferation. In addition, the changes in cell cycle related proteins were detected by western blot. Results: PIMREG was highly expressed in human ccRCC and was positively correlated with pathologic stage, TNM stage and histologic grade. In addition, patients with high expression of PIMREG had a poor prognosis. Univariable and multivariable Cox regression analysis identified that PIMREG was an independent prognostic factor of ccRCC. Additionally, PIMREG was also closely related to immune cell infiltration. Experiments in vitro identified that the knockdown of PIMREG could significantly inhibit the proliferation, migration and invasion abilities of ccRCC. The expression of cyclin D1, CDK4 and CDK6 was also significantly reduced after PIMREG knockdown. Conclusions: PIMREG plays a vital role in the development of ccRCC and may become a potential therapeutic target in the future.